Comparative physicochemical and rheological properties of tamarind seed xyloglucan from sweet and sour tamarind cultivars for food applications - Julapuk, Punwadee; Sriprom, Pongsert; Narkrugsa, Woatthichai; Phumjan, Lamphung; Adair, Pornpatu; Oomnog, Niroth; Manamoongmongkol, Kanjana; Bunyarit, Nagorn; Assawasaengrat, Pornsawan (My University, 2026)
This study comparatively investigated the physicochemical, structural, and rheological properties of xyloglucan extracted from sweet (Sri Chomphu) and sour (Kradan) tamarind kernel (TKP) cultivated in Thailand to provide insights for industrial applications. The extraction yields were 58.35 ± 0.28% and 57.90 ± 0.37% (w/w) for sweet and sour TKP, respectively. Chemical composition analysis revealed comparable macronutrient profiles between the two samples. FTIR spectra confirmed similar functional groups, while SEM analysis showed amorphous and heterogeneous structures with slight differences in porosity. Molecular weight distribution indicated that sour TKP-derived xyloglucan was dominated by intermediate molecular weight fractions (4.03 × 10⁵ Da, 70.46%), whereas sweet TKP-derived xyloglucan exhibited a broader distribution. These structural differences influenced hydration properties, with sweet xyloglucan showing significantly higher water absorption and solubility (%WAI: 475.02 ± 9.91%; %WSI: 5.62 ± 0.62%) compared to sour xyloglucan (%WAI: 398.81 ± 7.01%; %WSI: 4.81 ± 0.57%). Evaluation of gelling properties revealed that both samples exhibited maximum gel strength at 2% concentration and pH 3, with sour xyloglucan forming stronger gels. Rheological analysis demonstrated non-Newtonian pseudoplastic behavior and dominant elastic characteristics (G′ ' G″), with higher viscosity observed in the sour cultivar. Emulsifying activity and stability were high and showed no significant differences (EA: 93.58–94.87%; ES: 97.94–98.71%). Overall, while cultivar origin had minimal impact on structural and emulsifying properties, it significantly influenced hydration and gelling-related characteristics, supporting the potential of tamarind xyloglucan as a versatile hydrocolloid for food and material applications.
Keywords: Hydration properties; Plant-derived hydrocolloid; Polysaccharide functionality; Tamarind seed kernel; Viscoelastic behavior; Xyloglucan